Redescription of three Hippasa species from China (Araneae: Lycosidae), with a proposed species group-division and diagnosis - Wang, Lu-Yu; Li, Zong-Xu; Zhou, Ke-Xin; Zhang, Zhi-Sheng (Zootaxa, 2015)
The genus Hippasa is a group of web-weaving lycosids, whose web is funnel-like, quite similar to those of the Agelenidae. In this paper, based on published papers and specimens from China, we diagnose and discuss the composition of this genus. Two species groups are recognised, the Hippasa greenalliae-group (12 species and a subspecies) mainly from Asia and the Hippasa partita-group (17 species), which is distributed in both South Asia and Africa. In China, there are three Hippasa species: H. holmerae Thorell, 1895, H. lingxianensis Yin & Wang, 1980 (revalidated) and H. lycosina Pocock, 1900. The Japanese species, H. babai Tanikawa, 2007 is newly synonymised with H. lingxianensis. Two Hippasa species, H. agelenoides (Simon, 1884) and H. greenalliae (Blackwall, 1867) have never been found in China. Morphological illustrations, photos and redescriptions of H. holmerae, H. lingxianensis and H. lycosina are provided, based on Chinese specimens.